Analisis Du Pont System terhadap Performa Finansial 4 Perusahaan Semen di BEI untuk Periode 2013-2023 - Adinda Shefiyah Nur Izza; Neneng Miskiyah; Dewi Fadila (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to evaluate the financial performance of four cement companies listed on the Indonesia Stock Exchange (IDX) during the 2013 period. To achieve this, a descriptive quantitative approach was employed, utilizing purposive sampling. Data for the study was gathered from annual financial reports, which were publicly accessible through the official websites of the IDX and the individual companies. The analysis was carried out using the Du Pont System, a method that decomposes return on equity (ROE) into its components to assess the financial performance of the companies. The results of the analysis reveal that PT Inisial A exhibited the strongest financial performance among the four companies, demonstrating superior efficiency, profitability, and leverage. Following PT Inisial A, PT Inisial X performed moderately well, showing stable financial health but with some room for improvement in certain areas. On the other hand, PT Inisial Y and PT Inisial Z displayed the weakest performance, with PT Inisial Z facing significant challenges in maintaining profitability and managing its assets efficiently. This study’s findings provide valuable insights for investors, as it highlights the financial strengths and weaknesses of the companies involved, assisting them in making more informed investment decisions. Additionally, the results can serve as a reference for other companies within the cement industry, allowing them to identify areas for improvement and potential strategies for enhancing their financial performance. Furthermore, the research may contribute to future academic studies on corporate financial performance, particularly in the context of the cement industry in Indonesia. Overall, this research is expected to benefit both practitioners and academics by providing a comprehensive analysis of the financial status of the companies in question.